The importance and constraints of using mathematics teaching and learning sites from the point of view of mathematics teachers in the middle stage in Riyadh - Al-Saeed, Asmaa Nasser; Al-Daghim, Amal Suleiman; Al-Dasimani, Samar Fahad; Al-Babtain, Nada Abdulaziz (Journal of Educational and Psychological Sciences, 2017)
The aim of this research is to find out the extent to which the mathematics teachers of the intermediate stage benefit from the teaching and learning sites of mathematics, and to find the most used sites by mathematics teachers, and then study and evaluate these sites in the light of technical and educational standards for educational sites. The researchers used two tools to collect the study information, a questionnaire to identify the extent to which they benefited from the learning and learning sites of mathematics, and an evaluation form to determine the extent to which these sites are subject to technical and educational controls. The researcher applied the research using descriptive method, with the sample of the research divided into two parts: a human sample of (14) teachers of mathematics for the middle stage in Riyadh city, the second was an electronic sample of (5) mathematical sites, the research concluded the importance of these sites for the parameters , And the evaluation form showed the availability of technical and educational standards in these sites. The research recommended the establishment of a database of these educational sites on the Internet, so that teachers can benefit from them, and the need for teachers, especially mathematics teachers, to understand the importance of these sites as an activity that serves the educational content.
Keywords: calendar; websites; teaching mathematics